Parkinson’s Disease: No Milk Today? - Kistner, Andrea; Krack, Paul (Frontiers in Neurology, 2014)
Several prospective epidemiological studies on large cohorts have consistently reported an association between milk intake and a higher incidence of Parkinson’s disease (PD). Pesticide contamination of milk and milk’s urate-lowering effects have been put forward as risk factors to explain epidemiological data. This has led to considerable uncertainty among physicians and avoidance of dairy products by PD patients. However, neither factor stands up to the rational and detailed examination of the literature carried out in this mini-review. We suggest that changes in eating behavior related to premotor PD are an alternative potential explanation of correlations observed between milk intake and PD occurrence. Despite clear-cut associations between milk intake and PD incidence, there is no rational explanation for milk being a risk factor for PD. Based on current knowledge, limiting the consumption of dairy products does not seem to be a reasonable strategy in the prevention of the development and progression of PD.